An Investigation of the Validity of the Edinburgh Social Cognition Test (ESCoT) in Acquired Brain Injury (ABI). (19th November 2022) - Poveda, Blanca; Abrahams, Sharon; Baksh, R. Asaad; MacPherson, Sarah E.; Evans, Jonathan J.
Abstract: Objectives: Social cognition is frequently impaired following an acquired brain injury (ABI) but often overlooked in clinical assessments. There are few validated and appropriate measures of social cognitive abilities for ABI patients. The current study examined the validity of the Edinburgh Social Cognition Test (ESCoT, Baksh et al., 2018 ) in measuring social cognition following an ABI. Methods: Forty-one patients with ABI were recruited from a rehabilitation service and completed measures of general ability, executive functions and social cognition (Faux Pas; FP, Reading the Mind in the Eyes; RME, Social Norms Questionnaire; SNQ and the ESCoT). Forty-one controls matched on age, sex and years of education also performed the RME, SNQ and ESCoT. Results: A diagnosis of ABI was significantly associated with poorer performance on all ESCoT measures and RME while adjusting for age, sex and years of education. In ABI patients, the ESCoT showed good internal consistency with its subcomponents and performance correlated with the other measures of social cognition demonstrating convergent validity. Better Trail Making Test performance predicted better ESCoT total, RME and SNQ scores. Higher TOPF IQ was associated with higher RME scores, while higher WAIS-IV working memory predicted better FP performance. Conclusions: The ESCoT is a brief, valid and internally consistent assessment tool able to detect social cognition deficits in neurological patients. Given the prevalence of social cognition deficits in ABI and the marked impact these can have on an individual's recovery, this assessment can be a helpful addition to a comprehensive neuropsychological assessment.